Sexuality & gender for mental health professionals : a practical guide - Richards, Christina (Sage Publications Limited, 2013)
Examines the complexities of sexuality and gender, detailing the common and many of the less common sexualities, genders, and relationship forms, and explains experiences and issues relating to each.